Coating composition and coating film forming method

The coating composition addresses low solid content and adhesion issues by using a specific polyester resin and acrylic resin blend with blocked polyisocyanate, enhancing adhesion and finish quality on plastic substrates.

JP7619935B2Active Publication Date: 2025-01-22KANSAI PAINT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021507203
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-15
Filing Date
2020-03-06
Publication Date
2025-01-22
Estimated Expiration
2040-03-06

AI Technical Summary

Technical Problem

Existing coating compositions for plastic materials suffer from low solid content during application and inadequate adhesion, particularly when diluted for air spray coating, leading to insufficient adhesion and finish quality.

Method used

A coating composition comprising a polyester resin with specific glass transition temperature, weight average molecular weight, and hydroxyl value, combined with acrylic resins and a blocked polyisocyanate compound, along with pigments, to achieve high solid content and excellent adhesion to plastic substrates.

Benefits of technology

The composition allows for high solid content application with improved adhesion and finish quality, reducing environmental impact while maintaining excellent adhesion to various plastic materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007619935000001
    Figure 0007619935000001
  • Figure 0007619935000002
    Figure 0007619935000002
  • Figure 0007619935000003
    Figure 0007619935000003
Patent Text Reader

Abstract

This coating composition includes: a polyester resin (A) having a glass transition temperature from -70°C to 0°C, a weight-average molecular weight of 2,000-30,000, and a hydroxyl value of 30-150 mg KOH / g; an acrylic resin (B1) having a glass transition temperature of 50-90°C, a weight-average molecular weight of 5,000-10,000, and a hydroxyl value of 20-150 mg KOH / g, the acrylic resin (B1) having, as copolymer components, 65-80 mass% of methyl methacrylate (a), 5-35 mass% of a hydroxyl-group-containing polymerizable unsaturated monomer (b), and 0-30 mass% of another polymerizable unsaturated monomer (c); an acrylic resin (B2) having a glass transition temperature of 10-50°C, a weight-average molecular weight of 10,000-30,000, and a hydroxyl value of 80-150 mg KOH / g, the acrylic resin (B2) having, as copolymer components, 20-45 mass% of styrene (d), 10-35 mass% of a hydroxyl-group-containing polymerizable unsaturated monomer (e), and 20-70 mass% of another polymerizable unsaturated monomer (f); a blocked isocyanate compound (C); and a pigment (D).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a coating composition and a method for forming a coating film. [Background technology]

[0002] In various industrial products such as automobiles, various plastic materials are often used because of their light weight, strength, and excellent moldability. These plastic materials may be coated with paint to impart water resistance and weather resistance and to enhance their aesthetic appeal. In such cases, a coating composition suitable for the plastic material has usually been applied.

[0003] For example, Patent Document 1 describes a coating method in which a one-component base coat paint (A) containing, in a specific ratio, (a) a polyester resin, (b) an acrylic resin obtained by copolymerizing a monomer mixture containing 30 to 80% by weight of methyl methacrylate and having a glass transition temperature of 20 to 90°C, a weight average molecular weight of 5,000 to 50,000, and a hydroxyl value of 30 to 150 mgKOH / g, and (c) a blocked polyisocyanate is coated on a plastic molded product, and then a two-component clear coat paint (B) is coated on top of the base coat paint. Patent Document 2 describes a method for coating a plastic molding, which comprises coating the plastic molding with a one-component base coating material (A) containing a polyester polyol (a) having a static glass transition temperature of -80 to 0°C and a hydroxyl value of 40 to 120, and an aliphatic and / or alicyclic blocked polyisocyanate (b) in which an isocyanurate-type polyisocyanate modified with a hydroxyl compound is blocked with a dialkyl malonate and an acetoacetate, and then coating the coated surface with a two-component acrylic resin-based clear coating material (B) containing an acrylic resin (c) and a polyisocyanate (d) having a static glass transition temperature of -20 to +40°C, a hydroxyl value of 100 to 180, and a weight-average molecular weight of 4,000 to 15,000. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2004-154625 [Patent Document 2] Japanese Patent Application Publication No. 2002-119911 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the base coat paints described in Patent Documents 1 and 2 have a low solid content at the time of painting, and there is a risk of insufficient adhesion when applied to various plastic materials. In particular, when a metallic base coat paint is diluted to a painting viscosity required for good atomization in air spray painting, the coating solid content must be set to 30 mass% or less.

[0006] The object of the present invention is to provide a coating composition and a coating film forming method which can form a base coat film having a high coating solids content, excellent adhesion to materials, particularly to various plastic substrates, and excellent finish. [Means for solving the problem]

[0007] The present invention relates to the following items 1 to 6. 1. A polyester resin (A) having a glass transition temperature of -70 to 0°C, a weight average molecular weight of 2,000 to 30,000, and a hydroxyl value of 30 to 150 mgKOH / g; An acrylic resin (B1) containing 65 to 80 mass % of methyl methacrylate (a), 5 to 35 mass % of a hydroxyl group-containing polymerizable unsaturated monomer (b) and 0 to 30 mass % of other polymerizable unsaturated monomers (c) as copolymerization components, and having a glass transition temperature of 50 to 90°C, a weight average molecular weight of 5,000 to 10,000 and a hydroxyl value of 20 to 150 mgKOH / g; An acrylic resin (B2) containing 20 to 45 mass% of styrene (d), 10 to 35 mass% of a hydroxyl group-containing polymerizable unsaturated monomer (e) and 20 to 70 mass% of other polymerizable unsaturated monomers (f) as copolymerization components, the resin having a glass transition temperature of 10 to 50°C, a weight average molecular weight of 10,000 to 30,000 and a hydroxyl value of 80 to 150 mgKOH / g; A blocked polyisocyanate compound (C), and At least one pigment (D) selected from the group consisting of color pigments and luster pigments. A coating composition comprising: 2. The coating composition according to Item 1, wherein the content of the polyester resin (A) is within a range of 5 to 50 mass% based on the total resin solid content of the polyester resin (A), the acrylic resin (B1), the acrylic resin (B2), and the blocked polyisocyanate compound (C). 3. The coating composition according to item 1 or 2, further comprising at least one resin component (E) selected from the group consisting of non-aqueous dispersion resins and resin particles. 4. The coating composition according to item 1 or 2, further comprising a polyisocyanate compound (F). 5. A method for forming a coating film, comprising coating a plastic molded product with the coating composition according to any one of items 1 to 4. 6. The method for forming a coating film according to item 5, further comprising coating a two-liquid urethane clear coating on the coating film obtained by coating the coating composition according to any one of items 1 to 4. Effect of the Invention

[0008] The coating composition and coating film forming method of the present invention make it possible to form a basecoat coating film that has a high coating solids content, which reduces the environmental impact, has excellent adhesion to materials, particularly to various plastic substrates, and has an excellent finish. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present invention will be described in detail below, however, these are examples of preferred embodiments, and the present invention is not limited to the contents thereof. In this specification, "mass" is synonymous with "weight".

[0010] The coating composition of the present invention contains a polyester resin (A) having a glass transition temperature in the range of -70 to 0°C, a weight average molecular weight in the range of 2,000 to 30,000 and a hydroxyl value in the range of 30 to 150 mgKOH / g.

[0011] The polyester resin (A) can usually be obtained by esterifying a polybasic acid and a polyhydric alcohol with an excess of hydroxyl groups in a manner known per se.

[0012] The polybasic acid is a compound having two or more carboxyl groups in one molecule, and examples thereof include aromatic polybasic acids and their anhydrides, such as terephthalic acid, isophthalic acid, phthalic acid, naphthalenedicarboxylic acid, 4,4'-biphenyldicarboxylic acid, and diphenylmethane-4,4'-dicarboxylic acid; alicyclic dicarboxylic acids and their anhydrides, such as hexahydroisophthalic acid, hexahydroterephthalic acid, hexahydrophthalic acid, and tetrahydrophthalic acid; adipic acid, sebacic acid, suberic acid, succinic acid, glutaric acid, and the like. Examples of polybasic acids include aliphatic polybasic acids and anhydrides thereof, such as maleic acid, chloromaleic acid, fumaric acid, dodecanedioic acid, pimelic acid, azelaic acid, itaconic acid, citraconic acid, and dimer acid; lower alkyl esters, such as methyl esters and ethyl esters, of these dicarboxylic acids; and trivalent or higher polybasic acids, such as trimellitic acid, trimellitic anhydride, pyromellitic acid, pyromelic anhydride, trimesic acid, methylcyclohexene tricarboxylic acid, and tetrachlorohexene polybasic acid and anhydrides.

[0013] The polyhydric alcohol is a compound having two or more hydroxyl groups in one molecule, and examples thereof include ethylene glycol, propylene glycol, diethylene glycol, trimethylene glycol, tetraethylene glycol, triethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 2,3-butanediol, 1,2-butanediol, 3-methyl-1,2-butanediol, 1,2-pentanediol, 1,5-pentanediol, 1,4-pentanediol, 2,4- Dihydric alcohols such as pentanediol, 2,3-dimethyltrimethylene glycol, tetramethylene glycol, 3-methyl-4,3-pentanediol, 3-methyl-4,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,6-hexanediol, 1,5-hexanediol, 1,4-hexanediol, 2,5-hexanediol, neopentyl glycol, and hydroxypivalic acid neopentyl glycol ester; these dihydric alcohols and ε-caprolactone, etc. polyether diols such as alkylene oxide adducts of bisphenol A, polyethylene glycol, polypropylene glycol, and polybutylene glycol; α-olefin epoxides such as propylene oxide and butylene oxide, and monoepoxy compounds such as Cardura E10 (trade name, glycidyl ester of synthetic highly branched saturated fatty acid, manufactured by Shell Chemical Co., Ltd.); trihydric or higher alcohols such as glycerin, trimethylolpropane, trimethylolethane, diglycerin, triglycerin, 1,2,6-hexanetriol, pentaerythritol, dipentaerythritol, sorbitol, and mannitol; polylactone polyols obtained by adding lactones such as ε-caprolactone to these trihydric or higher alcohols; and alicyclic polyhydric alcohols such as 1,4-cyclohexanedimethanol, tricyclodecanedimethanol, hydrogenated bisphenol A, and hydrogenated bisphenol F.

[0014] The introduction of hydroxyl groups into the polyester resin (A) can be carried out, for example, by using a polyhydric alcohol having three or more hydroxyl groups in one molecule in combination. In addition, when reacting the polybasic acid with the polyhydric alcohol, a monobasic acid, an oil component (including its fatty acid), etc. may be used as necessary. Examples of the monobasic acid include benzoic acid and t-butylbenzoic acid, and examples of the oil component include castor oil, dehydrated castor oil, safflower oil, soybean oil, linseed oil, tall oil, coconut oil, and their fatty acids, and these can be used alone or in combination. Furthermore, the polyester resin may be modified with an epoxy compound such as butyl glycidyl ether, alkylphenyl glycidyl ether, or neodecanoic acid glycidyl ester, if necessary.

[0015] In the present invention, from the viewpoints of adhesion to plastic materials, water resistance and finish of the resulting coating film, and adjustment of the coating solids content of the coating composition, the polyester resin (A) has a glass transition temperature in the range of -70 to 0°C, preferably -60 to -20°C, a weight average molecular weight in the range of 2,000 to 30,000, preferably 2,000 to 20,000, and a hydroxyl value in the range of 30 to 150 mgKOH / g, preferably 40 to 100 mgKOH / g. By containing a polyester resin (A) having a glass transition temperature, weight average molecular weight and hydroxyl value in the above ranges, the coating solids content can be increased and adhesion to materials and finish can be improved.

[0016] In this specification, the glass transition temperature of the polyester resin is determined by differential scanning calorimetry (DSC).

[0017] In this specification, the weight average molecular weight and number average molecular weight are values ​​obtained by converting the retention time (retention volume) measured using a gel permeation chromatograph (GPC) into the molecular weight of polystyrene using the retention time (retention volume) of a standard polystyrene with a known molecular weight measured under the same conditions. Four columns, "TSKgel G-4000H×L", "TSKgel G-3000H×L", "TSKgel G-2500H×L", and "TSKgel G-2000H×L" (all of which are product names manufactured by Tosoh Corporation), were used, and the conditions were mobile phase: tetrahydrofuran, measurement temperature: 40° C., flow rate: 1 ml / min, and detector: RI.

[0018] From the viewpoints of adhesion to plastic materials, water resistance, finish, and the like of the coating film obtained by painting, the content of the polyester resin (A) is preferably within the range of 5 to 50 mass %, and more preferably within the range of 10 to 40 mass %, based on the total resin solid content of the polyester resin (A), the acrylic resin (B1) and the acrylic resin (B2) described below, and the blocked polyisocyanate compound (C).

[0019] From the viewpoints of adhesion of the resulting coating film to plastic materials, water resistance, finish, etc., the coating composition of the present invention contains an acrylic resin (B1) having copolymerization components of 65 to 80 mass %, preferably 70 to 80 mass %, of methyl methacrylate (a), 5 to 35 mass %, preferably 10 to 30 mass %, of a hydroxyl group-containing polymerizable unsaturated monomer (b), and 0 to 30 mass %, preferably 5 to 25 mass %, of other polymerizable unsaturated monomers (c).

[0020] The acrylic resin (B1) can usually be obtained by copolymerizing the above-mentioned polymerizable unsaturated monomers by a polymerization method known per se, such as solution polymerization.

[0021] Examples of the hydroxyl group-containing polymerizable unsaturated monomer (b) include monoesters of polyhydric alcohols and (meth)acrylic acid, such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, polyethylene glycol mono(meth)acrylate, and polypropylene glycol (meth)acrylate, and compounds obtained by ring-opening polymerization of the monoesters of polyhydric alcohols and (meth)acrylic acid with ε-caprolactone, and the like. These can be used alone or in combination of two or more kinds.

[0022] Examples of the other polymerizable unsaturated monomers (c) include (meth)acrylates such as methyl acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl acrylate, cyclohexyl (meth)acrylate, n-octyl (meth)acrylate, lauryl (meth)acrylate, isobornyl (meth)acrylate, and stearyl (meth)acrylate. Alkyl esters of acrylic acid; carboxyl group-containing polymerizable unsaturated monomers such as (meth)acrylic acid, maleic acid, and maleic anhydride; aminoalkyl (meth)acrylates such as N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylate; acrylamide, methacrylamide, N,N-dimethylaminoethyl (meth)acrylamide, N,N-diethylaminoethyl (meth)acrylamide, and N,N-dimethylaminopropyl (meth)acrylate; (meth)acrylamide or its derivatives such as N-methylolacrylamide, N-methylolacrylamide methyl ether, and N-methylolacrylamide butyl ether; quaternary ammonium base-containing monomers such as 2-(methacryloyloxy)ethyltrimethylammonium chloride and 2-(methacryloyloxy)ethyltrimethylammonium bromide; (meth)acrylamido-alkanesulfonic acids such as 2-acrylamido-2-methylpropanesulfonic acid, and sulfoalkyl (meth)acrylates such as 2-sulfoethyl (meth)acrylate; acrylonitrile, methacrylonitrile, vinyl acetate, styrene, vinyl toluene, α-methylstyrene; polyvinyl compounds such as allyl methacrylate; hydrolyzable silyl group-containing polymerizable unsaturated monomers such as -(meth)acryloyloxypropyltrimethoxysilane, γ-(meth)acryloyloxypropyltriethoxysilane, and γ-(meth)acryloyloxypropylmethyldimethoxysilane, and the like. These may be used alone or in combination of two or more.

[0023] In this specification, "(meth)acrylate" means acrylate or methacrylate, "(meth)acrylic acid" means acrylic acid or methacrylic acid, "(meth)acryloyl" means acryloyl or methacryloyl, and "(meth)acrylamide" means acrylamide or methacrylamide.

[0024] The copolymerization of the polymerizable unsaturated monomer is preferably carried out by a solution polymerization method. For example, a mixture of the polymerizable unsaturated monomer and a radical polymerization initiator is dissolved or dispersed in an organic solvent, and usually heated at a temperature of about 80° C. to about 200° C. for about 1 to 10 hours with stirring to polymerize the mixture.

[0025] The acrylic resin (B1) obtained as described above has a glass transition temperature of 50 to 90° C., preferably 60 to 80° C., a weight average molecular weight of 5,000 to 10,000, preferably 6,000 to 9,000, and a hydroxyl value of 20 to 150 mgKOH / g, preferably 30 to 120 mgKOH / g, from the viewpoints of adhesion to plastic materials, water resistance, and finish of the coating film obtained by applying the coating composition of the present invention, as well as adjustment of the coating solids content of the coating composition. By containing an acrylic resin (B1) having a glass transition temperature, weight average molecular weight, and hydroxyl value in the above ranges, the coating solids content can be increased, and adhesion to materials and finish can be improved.

[0026] In this specification, the glass transition temperature Tg of the acrylic resin is a value calculated by the following formula. 1 / Tg(K)=W1 / T1+W2 / T2+...Wn / Tn Tg(℃)=Tg(K)-273 In the formula, W1, W2, ... Wn are the mass fractions of each monomer, and T1, T2 ... Tn are the glass transition temperatures Tg (K) of the homopolymers of each monomer. The glass transition temperatures of the homopolymers of each monomer are values ​​according to POLYMER HANDBOOK Fourth Edition, edited by J. Brandrup, Eh Immergut, and EA Grulke (1999). For the glass transition temperatures of monomers not described in the literature, the values ​​used are those obtained by synthesizing a homopolymer of the monomer so that the weight average molecular weight is about 50,000 and measuring the glass transition temperature by differential scanning calorimetry.

[0027] In the coating composition of the present invention, the content of the acrylic resin (B1) is preferably within the range of 5 to 40 mass %, more preferably 5 to 30 mass %, based on the total resin solid content of the polyester resin (A), the acrylic resin (B1), the acrylic resin (B2) and the blocked polyisocyanate compound (C), from the viewpoints of adhesion to plastic materials, water resistance, finish, etc. of the resulting coating film.

[0028] From the viewpoints of adhesion of the resulting coating film to plastic materials, water resistance, finish, etc., the coating composition of the present invention contains an acrylic resin (B2) having copolymerization components of 20 to 45 mass %, preferably 25 to 40 mass %, of styrene (d), 10 to 35 mass %, preferably 15 to 30 mass %, of a hydroxyl group-containing polymerizable unsaturated monomer (e), and 20 to 70 mass %, preferably 30 to 60 mass %, of other polymerizable unsaturated monomers (f).

[0029] The hydroxyl-containing polymerizable unsaturated monomer (e) can be appropriately selected from the hydroxyl-containing polymerizable unsaturated monomers (b) listed above.

[0030] The other polymerizable unsaturated monomer (f) is a monomer or oligomer having an ethylenically unsaturated group that can be copolymerized with styrene (d) or the hydroxyl group-containing polymerizable unsaturated monomer (e), and examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, 2-ethylhexyl acrylate, cyclohexyl (meth)acrylate, and n-octyl (meth)acrylate. alkyl esters of (meth)acrylic acid, such as (meth)acrylic acid, lauryl (meth)acrylate, isobornyl (meth)acrylate, and stearyl (meth)acrylate; carboxyl group-containing polymerizable unsaturated monomers, such as (meth)acrylic acid, maleic acid, and maleic anhydride; aminoalkyl (meth)acrylates, such as N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylate; acrylamide, methacrylamide, and N,N-dimethylaminoethyl (meth)acrylate; (Meth)acrylamide, N,N-diethylaminoethyl (meth)acrylamide, N,N-dimethylaminopropyl (meth)acrylamide, N-methylolacrylamide, N-methylolacrylamide methyl ether, N-methylolacrylamide butyl ether and other (meth)acrylamides or derivatives thereof; 2-(methacryloyloxy)ethyltrimethylammonium chloride, 2-(methacryloyloxy)ethyltrimethylammonium bromide and other quaternary ammonium base-containing monomers; 2-acrylamido-2-methyl (Meth)acrylamido-alkanesulfonic acids such as propanesulfonic acid, sulfoalkyl (meth)acrylates such as 2-sulfoethyl (meth)acrylate, acrylonitrile, methacrylonitrile, vinyl acetate, vinyl toluene, α-methylstyrene, polyvinyl compounds such as allyl methacrylate, hydrolyzable silyl group-containing polymerizable unsaturated monomers such as γ-(meth)acryloyloxypropyltrimethoxysilane, γ-(meth)acryloyloxypropyltriethoxysilane, γ-(meth)acryloyloxypropylmethyldimethoxysilane, etc.Examples of the oligomer include (meth)acrylates having a polyoxyalkylene chain whose molecular terminal is an alkoxy group, and these can be used alone or in combination of two or more. In addition, as the oligomer, for example, those obtained by introducing an ethylenically unsaturated group into various resins such as acrylic, polyester, and polyurethane can be used. Specific examples include a resin obtained by adding glycidyl (meth)acrylate to an acrylic resin or polyester resin having a carboxyl group, a resin obtained by adding maleic anhydride or itaconic anhydride to a vinyl resin or polyester resin having a hydroxyl group, a resin obtained by adding (meth)acrylic acid to an acrylic resin having an epoxy group, a resin obtained by condensing (meth)acrylic acid to a polyester resin having a hydroxyl group, an unsaturated polyester resin, and a resin obtained by adding 2-hydroxyethyl (meth)acrylate to a urethane resin having an isocyanate group.

[0031] The copolymerization of the polymerizable unsaturated monomer is preferably carried out by a solution polymerization method. For example, a mixture of the polymerizable unsaturated monomer and a radical polymerization initiator is dissolved or dispersed in an organic solvent, and usually heated at a temperature of about 80° C. to about 200° C. for about 1 to 10 hours with stirring to polymerize the mixture.

[0032] The acrylic resin (B2) obtained as described above has a glass transition temperature in the range of 10 to 50°C, preferably 15 to 40°C, a weight average molecular weight in the range of 10,000 to 30,000, preferably 10,000 to 25,000, and a hydroxyl value in the range of 80 to 150 mgKOH / g, preferably 90 to 130 mgKOH / g, from the viewpoints of adhesion to plastic materials, water resistance, finish, etc. of a coating film obtained by applying the coating composition of the present invention.

[0033] In the coating composition of the present invention, the content of the acrylic resin (B2) is preferably within the range of 10 to 60 mass %, more preferably 15 to 55 mass %, based on the total resin solid content of the polyester resin (A), the acrylic resin (B1), the acrylic resin (B2) and the blocked polyisocyanate compound (C), from the viewpoints of adhesion to plastic materials, water resistance, finish, and the like of the resulting coating film.

[0034] The coating composition of the present invention contains a blocked polyisocyanate compound (C) from the viewpoint of the water resistance and weather resistance of the coating film obtained by coating.

[0035] The blocked polyisocyanate compound (C) is a polyisocyanate compound to which a blocking agent has been added, and is stable at room temperature. However, when heated to the baking temperature of the coating film (usually about 80 to about 200°C), the blocking agent dissociates, and free isocyanate groups can be regenerated.

[0036] Examples of the polyisocyanate compound include aliphatic polyisocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, dimer acid diisocyanate, and lysine diisocyanate; biuret type adducts, isocyanurate ring adducts, allophanate type adducts, and uretdione type adducts of these aliphatic polyisocyanates; alicyclic diisocyanates such as isophorone diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and methylcyclohexane-2,4- or -2,6-diisocyanate; biuret type adducts and isocyanurate ring adducts of these alicyclic diisocyanates; xylylene diisocyanate, tetramethylxylylene diisocyanate, tolylene Examples of the aromatic diisocyanate compounds include diisocyanates, 4,4'-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate, and 1,4-naphthalene diisocyanate; biuret-type adducts and isocyanurate ring adducts of these aromatic diisocyanates; hydrogenated MDI and derivatives of hydrogenated MDI; urethane adducts obtained by reacting a polyisocyanate compound with a hydroxyl group of a polyol such as ethylene glycol, propylene glycol, 1,4-butylene glycol, dimethylolpropionic acid, polyalkylene glycol, trimethylolpropane, or hexanetriol in a ratio such that an excess of isocyanate groups is present; and biuret-type adducts and isocyanurate ring adducts of these urethane adducts.

[0037] Examples of blocking agents include phenol-based, lactam-based, alcohol-based, ether-based, oxime-based, active methylene-based, mercaptan-based, acid amide-based, imide-based, amine-based, imidazole-based, and pyrazole-based blocking agents.

[0038] As the blocked polyisocyanate compound (C) used in the present invention, particularly, blocked polyisocyanate compounds using active methylene-based or pyrazole-based blocking agents can be suitably used.

[0039] In the coating composition of the present invention, the content of the blocked polyisocyanate compound (C) is preferably within the range of 10 to 50 parts by mass, more preferably 15 to 45% by mass, based on the total resin solids content of the polyester resin (A), acrylic resin (B1), acrylic resin (B2) and blocked polyisocyanate compound (C), from the viewpoints of adhesion to plastic materials, water resistance, finish, etc. of the resulting coating film.

[0040] The coating composition of the present invention contains at least one pigment (D) selected from the group consisting of color pigments and luster pigments. Examples of color pigments include white pigments such as titanium oxide, black pigments such as carbon black, acetylene black, lamp black, bone black, graphite, iron black, and aniline black, yellow pigments such as yellow iron oxide, titanium yellow, monoazo yellow, condensed azo yellow, azomethine yellow, bismuth vanadate, benzimidazolone, isoindolinone, isoindoline, quinophthalone, benzidine yellow, and permanent yellow, orange pigments such as permanent orange, red iron oxide, naphthol AS azo red, anthanthrone, anthraquinonyl red, perylene maroon, quinacridone red pigments, diketopyrrolopyrrole, watching red, and permanent red, purple pigments such as cobalt purple, quinacridone violet, and dioxazine violet, blue pigments such as cobalt blue, phthalocyanine blue, and threne blue, and green pigments such as phthalocyanine green.

[0041] Examples of the glittering pigment include metallic pigments and optical interference pigments. Representative examples of the metallic pigment include uncolored or colored metallic glitters made of metals or alloys such as aluminum, aluminum oxide, copper, zinc, iron, nickel, and tin, and also include special metal-deposited film flakes. Examples of the optical interference pigment include mica, mica surface-coated with metal oxide, micaceous iron oxide, graphite pigments, and hologram pigments, which can be used alone or in combination of two or more.

[0042] In the coating composition of the present invention, the content of the pigment (D) is preferably within the range of 1 to 200 mass %, more preferably within the range of 2 to 100 mass %, and even more preferably within the range of 5 to 50 mass %, based on the total resin solids content of the polyester resin (A), the acrylic resin (B1), the acrylic resin (B2) and the blocked polyisocyanate compound (C), from the viewpoints of adhesion to plastic materials, water resistance, finish, and the like of the resulting coating film.

[0043] The coating composition of the present invention may contain at least one resin component (E) selected from the group consisting of non-aqueous dispersion resins and resin particles, if necessary. The resin component (E) is usually used as a rheology control agent. The non-aqueous dispersion resin is obtained as a non-aqueous dispersion of a particulate polymer insoluble in an organic liquid obtained by polymerizing a radically polymerizable unsaturated monomer in an organic liquid in the presence of a polymeric dispersion stabilizer resin. The resin particles are obtained as a particulate polymer having an intramolecular crosslinked structure obtained by aqueous emulsion or aqueous suspension polymerization.

[0044] In the coating composition of the present invention, the content of the resin component (E) is preferably within the range of 1 to 20 mass %, more preferably within the range of 2 to 15 mass %, and even more preferably within the range of 5 to 15 mass %, based on the total resin solids content of the polyester resin (A), the acrylic resin (B1), the acrylic resin (B2) and the blocked polyisocyanate compound (C), from the viewpoint of the finish of the resulting coating film, etc.

[0045] The coating composition of the present invention may also contain a polyisocyanate compound (F) as required.

[0046] Examples of the polyisocyanate compound (F) include aliphatic polyisocyanates such as hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, dimer acid diisocyanate, and lysine diisocyanate; biuret type adducts, isocyanurate ring adducts, allophanate type adducts, and uretdione type adducts of these aliphatic polyisocyanates; alicyclic diisocyanates such as isophorone diisocyanate, 4,4'-methylenebis(cyclohexyl isocyanate), and methylcyclohexane-2,4- or -2,6-diisocyanate; biuret type adducts and isocyanurate ring adducts of these alicyclic diisocyanates; xylylene diisocyanate, tetramethylxylylene diisocyanate, trimethylcyclohexane diisocyanate, and trimethylcyclohexane diisocyanate. Examples of suitable diisocyanate compounds include aromatic diisocyanate compounds such as 1,4-naphthalene diisocyanate, 4,4'-diphenylmethane diisocyanate (MDI), 1,5-naphthalene diisocyanate, and 1,4-naphthalene diisocyanate; biuret-type adducts and isocyanurate ring adducts of these aromatic diisocyanates; hydrogenated MDI and derivatives of hydrogenated MDI; urethane adducts obtained by reacting a polyisocyanate compound with a hydroxyl group of a polyol such as ethylene glycol, propylene glycol, 1,4-butylene glycol, dimethylolpropionic acid, polyalkylene glycol, trimethylolpropane, or hexanetriol in a ratio such that an excess of isocyanate groups is present; and biuret-type adducts and isocyanurate ring adducts of these urethane adducts.

[0047] When the polyisocyanate compound (F) is used, the amount used is selected so that the isocyanate group (NCO) contained therein relative to the hydroxyl group (OH) in the polyester resin (A), the acrylic resin (B1) and the acrylic resin (B2) is in an NCO / OH equivalent ratio range of preferably 0.2 to 1.5, more preferably 0.5 to 1.0.

[0048] The coating composition of the present invention may further contain extender pigments, curing catalysts, organic solvents, cellulose derivatives, pigment dispersants, leveling agents, ultraviolet absorbers, light stabilizers, plasticizers, etc., as necessary.

[0049] Examples of extender pigments include baryta powder, precipitated barium sulfate, barium carbonate, calcium carbonate, gypsum, clay, silica, white carbon, diatomaceous earth, talc, magnesium carbonate, alumina white, gloss white, and mica powder.

[0050] Examples of the curing catalyst include organometallic compounds such as tin octylate, dibutyltin di(2-ethylhexanoate), dioctyltin di(2-ethylhexanoate), dioctyltin diacetate, dibutyltin dilaurate, dibutyltin oxide, dioctyltin oxide, dibutyltin fatty acid salt, lead 2-ethylhexanoate, zinc octylate, zinc naphthenate, zinc fatty acid, cobalt naphthenate, calcium octylate, copper naphthenate, and tetra(2-ethylhexyl) titanate, which can be used alone or in combination of two or more. These can also be used in combination with known urethane curing catalysts such as tertiary amines and phosphoric acid compounds as necessary. When a curing catalyst is contained, the content of the curing catalyst is preferably within the range of 0.001 to 2 parts by mass, more preferably 0.01 to 1 part by mass, relative to 100 parts by mass of the resin solid content in the coating composition.

[0051] The organic solvent is not particularly limited, and for example, typical paint solvents such as hydrocarbons, esters, ethers, alcohols, and ketones can be used.

[0052] The coating composition of the present invention can be applied to a variety of substrates, including metal plates such as iron plates, aluminum plates, brass plates, copper plates, stainless steel plates, tin plates, zinc-plated steel plates, and zinc alloy (Zn-Al, Zn-Ni, Zn-Fe, etc.)-plated steel plates; plastic materials such as resins such as polyethylene resin, polypropylene resin, acrylonitrile-butadiene-styrene (ABS) resin, polyamide resin, acrylic resin, vinylidene chloride resin, polycarbonate resin, polyurethane resin, and epoxy resin, as well as various FRPs; inorganic materials such as glass, cement, and concrete; wood; and fiber materials (paper, cloth, etc.). The coating composition of the present invention has particularly excellent adhesion to plastic molded products, and in the present invention, it is preferable to apply the coating composition to plastic molded products.

[0053] The plastic molded product is preferably, for example, an injection molded product or a film or sheet-shaped product made of at least one plastic material selected from the group consisting of ABS resin, polycarbonate resin, polycarbonate-ABS resin, acrylic resin, polystyrene resin, polyamide resin, and glass fiber reinforced resins thereof. In the coating film forming method of the present invention, these materials can be degreased or surface treated as appropriate to prepare the substrate.

[0054] In the present invention, the method of applying the coating composition is not particularly limited. For example, the coating composition can be applied by air spray, airless spray, rotary atomizing coater, dip coating, brush, etc. Electrostatic application may be performed during coating. The film thickness can be usually within the range of 3 to 50 μm, preferably 3 to 30 μm, and more preferably 5 to 20 μm as a dry film thickness. The coating composition of the present invention can increase the coating solid content, so it is also suitable for air spray coating. In particular, in the case of air spray coating, from the viewpoint of ensuring the finish and design, it is preferable to appropriately adjust the viscosity at the time of coating using a solvent such as an organic solvent so that the viscosity is in the range of about 5 to 30 seconds, preferably about 8 to 20 seconds, measured using a Ford Cup No. 4 viscometer at 20° C. In this case, it is preferable that the solid content concentration at the time of coating is 30 mass % or more, and particularly 30 to 40 mass %.

[0055] When the coating composition of the present invention is applied and then heat cured, the heating conditions are not particularly limited, but the composition can be cured by holding the composition at 50 to 100° C., preferably 50 to 90° C., for 10 to 90 minutes.

[0056] In the coating film forming method of the present invention, after the coating composition is applied, it is left to stand at room temperature for about 5 to 15 minutes, and then a clear coating, which will be described later, can be applied onto the uncured coating film.

[0057] The clear coating material that can be used in the coating film forming method of the present invention is preferably a two-liquid type urethane clear coating material that contains a hydroxyl-containing acrylic resin and a polyisocyanate compound. The two-liquid type coating material is composed of a base material that contains a hydroxyl-containing acrylic resin and a curing agent that contains a polyisocyanate compound, and the two can be mixed and applied immediately before use.

[0058] The coating method of the clear coating is not particularly limited, but for example, a wet coating film can be formed by a coating method such as air spray coating, airless spray coating, rotary atomization coating, curtain coat coating, etc. In these coating methods, electrostatic application may be performed optionally. Among them, air spray coating is particularly preferred. The film thickness of the clear coating is usually 10 to 50 μm, preferably 20 to 45 μm, as a cured film thickness. In addition, when performing air spray coating, airless spray coating, and rotary atomization coating, it is preferable to appropriately adjust the viscosity of the clear coating using a solvent such as an organic solvent so that it is in a viscosity range suitable for the coating, usually in a viscosity range of about 5 to 30 seconds at 20 ° C. using a Ford Cup # No. 4 viscometer.

[0059] The multi-layer coating film formed above, consisting of the coating film obtained by applying the coating composition of the present invention and the coating film obtained by applying the clear coating, can be heated by a conventional coating film baking method, such as hot air heating, infrared heating, high frequency heating, etc. The heating retention temperature (keep temperature) can be appropriately determined depending on the substrate, but is suitably within the range of 60 to 140°C, particularly 70 to 120°C. The heating retention time (keep time) is suitably within the range of 10 to 50 minutes, particularly 20 to 40 minutes. Before the above-mentioned bake hardening, optionally, setting may be performed at room temperature for about 1 to 60 minutes and / or preheating may be performed at a temperature of 40 to 80° C. for about 1 to 60 minutes. EXAMPLES

[0060] The present invention will be described in more detail below with reference to examples and comparative examples. However, the present invention is not limited to these examples. In addition, "parts" and "%" are all based on mass.

[0061] Polyester resin manufacturing example Manufacturing Example 1 In a reaction vessel equipped with a heating device, a stirrer, a thermometer, a rectification tower and a water separator, 69.4 parts of hexahydrophthalic anhydride, 73.1 parts of adipic acid, 106.4 parts of 1,6-hexanediol and 13.4 parts of trimethylolpropane were charged and heated, and the temperature was raised from 160°C to 230°C over 3 hours. This was kept at 230°C for 1 hour, and the generated condensed water was distilled off using a rectification tower. Next, 5 parts of xylene were added, and the condensed water was discharged using a water separator while maintaining reflux. When the acid value reached 8 mgKOH / g, the mixture was cooled to 120°C, and diluted with a mixed solvent of xylene / butyl acetate = 1 / 1 (mass ratio) to a solid content of 60%, to obtain a polyester resin (A-1) solution. The weight average molecular weight of polyester (A-1) was 15,000, the hydroxyl value was 56 mgKOH / g and the glass transition temperature was -57°C.

[0062] Manufacturing Examples 2-10 Solutions of polyester resins (A-2) to (A-10) were obtained in the same manner as in Production Example 1, except that the raw material composition in Production Example 1 was changed as shown in Table 1. The weight average molecular weight, hydroxyl value, and glass transition temperature of each polyester resin are shown in Table 1.

[0063] [Table 1]

[0064] Acrylic resin manufacturing example Manufacturing Example 11 In a reaction vessel equipped with a heating device, a stirrer, a thermometer, a reflux condenser, and a dropping device, 45.0 parts of butyl acetate were charged, and the mixture was stirred at 110°C while blowing in nitrogen gas. A mixture of 70.0 parts of methyl methacrylate, 10.0 parts of isobornyl acrylate, 5.0 parts of n-butyl methacrylate, 15.0 parts of hydroxyethyl acrylate, 10.0 parts of butyl acetate, and 6.0 parts of t-butylperoxy-2-ethylhexanate was dropped into the reaction vessel over 3 hours, and the mixture was further aged at the same temperature for 2 hours (first aging). Then, a mixture of 15.0 parts of butyl acetate and 1.0 part of t-butylperoxy-2-ethylhexanate was further dropped into the reaction vessel over 3 hours, and the mixture was aged for 1 hour after the end of the dropping (second aging). Then, the solution was cooled to 60°C, and diluted with methyl ethyl ketone to a solid content of 50% to obtain an acrylic resin (B1-1) solution. The resulting acrylic resin (B1-1) had a weight average molecular weight of 7,000, a hydroxyl value of 73 mgKOH / g, and a glass transition temperature of 61°C.

[0065] Manufacturing Examples 12-20 Solutions of acrylic resins (B1-2) to (B2-5) were obtained in the same manner as in Production Example 11, except that the raw material composition in Production Example 11 was changed as shown in Table 2. The weight average molecular weight, hydroxyl value, and glass transition temperature of each acrylic resin are shown in Table 2. In Production Examples 13, 17, and 19, t-butylperoxy-2-ethylhexanate was added in two separate batches in Production Example 1, instead of 2,2'-azobisisobutyronitrile.

[0066] [Table 2]

[0067] Preparation of base coat paint Examples 1 to 12 and Comparative Examples 1 to 15 The components shown in Table 3 were mixed uniformly, and a dilution solvent (butyl acetate / methyl ethyl ketone = 1 / 1 (mass ratio)) was added to adjust the viscosity to 15 seconds at 20°C using a Ford Cup No. 4 viscometer, to obtain each base coat paint. The amount of each component is based on the total resin solid content of the polyester resin (A), acrylic resin (B1), acrylic resin (B2), and blocked polyisocyanate compound (C). The coating solid content of each base coat paint after viscosity adjustment is shown in Table 3.

[0068] The ingredients in Table 3 are shown in solid content, and the blocked isocyanate compound (C), pigment (D), non-aqueous dispersion resin, polyisocyanate compound and surface conditioner ((*1) to (*8)) in Table 3 are as follows: (*1) C-1: "Duranate MF-K60X", product name, manufactured by Asahi Kasei Chemical Corporation, HDI-based active methylene-blocked polyisocyanate (*2) C-2: "Duranate E402-B80T", product name, manufactured by Asahi Kasei Chemical Corporation, HDI-based oxime-blocked polyisocyanate (*3) D-1: "Aluminum Paste 7N", product name, manufactured by Toyo Aluminum Co., Ltd., solid content 65% (*4) D-2: "6360NS", Toyo Aluminum Co., Ltd., aluminum paste, product name, solid content 69% (*5) D-3: "BP6360", Toyo Aluminum Co., Ltd., aluminum paste, product name, solid content 55%

[0069] (*6) E-1: Non-aqueous resin dispersion was prepared by the following method. 40 parts of isobutyl acetate and 40 parts of toluene were heated under reflux, and the following monomers and polymerization initiator were added dropwise over a period of 3 hours, and the mixture was then aged for 2 hours. Styrene 10 parts Isobutyl methacrylate 49 parts 2-Ethylhexyl methacrylate 30 parts 2-Hydroxyethyl methacrylate 11 parts Azobisisobutyronitrile 2 parts The obtained acrylic resin had a non-volatile content of 55%, a viscosity G (measured at 25° C. using a Gardner bubble viscometer, the same applies below), and a weight average molecular weight of 16,000. Next, 93 parts of heptane and 98 parts of the 55% dispersion stabilizer resin varnish, which is the acrylic resin obtained above, were charged into a flask and heated to reflux, and the following monomers and polymerization initiator were added dropwise over 3 hours, followed by aging for a further 2 hours. Styrene 15 parts Methyl methacrylate 40 parts Acrylonitrile 30 parts 2-Hydroxyethyl methacrylate 15 parts t-Butyl peroxy-2-ethylhexanoate 1.5 parts The obtained non-aqueous resin dispersion was a milky white, stable, low-viscosity polymer dispersion having a non-volatile content of 53%, a viscosity of B, and a polymer particle diameter (measured by electron microscope) of 0.2 to 0.3 μm.

[0070] (*7) F-1: "Coronate HXR", product name, manufactured by Tosoh Corporation, HDI isocyanurate type polyisocyanate (*8) Surface conditioner: "Disparlon LF-1985", manufactured by Kusumoto Chemicals Co., Ltd., surface conditioner, solid content 50%

[0071] [Table 3]

[0072] Preparation of test panels Each of the base coat paints of Examples 1 to 12 and Comparative Examples 1 to 15 was spray-painted on an ABS plate and a polycarbonate plate to a cured film thickness of 15 μm, and left at room temperature for 3 minutes. Then, "Soflex 900TH-1" (Kansai Paint Co., Ltd., acrylic urethane two-component clear paint) was spray-painted on the base coat paint to a dry film thickness of 35 μm, and cured by heating at 80°C for 20 minutes to obtain each test coated plate having a multi-layer coating film.

[0073] Each test plate was subjected to the following tests, and the results are shown in Table 3. (Note 1) Finishing properties: Each test coated plate (ABS plate) was visually observed, and the occurrence of metallic unevenness was evaluated according to the following criteria. A (Good): Almost no metallic unevenness is observed, and the coating has an extremely excellent appearance. B (Fair): Slight metallic unevenness is observed, but the coating has excellent appearance. C (Fail): Metallic unevenness is observed, and the coating appearance is somewhat poor. D (Fail): Metallic unevenness is evident, and the appearance of the coating is poor. (Note 2) Adhesion (initial): In accordance with JIS K 5600-5-6 (1990), 100 2 mm x 2 mm square grids were created on the coating surface of each test panel (ABS panel and polycarbonate panel), and adhesive tape was attached to the surface and then quickly peeled off, after which the number of square grid coatings remaining on the coating surface was counted. A (Good): Remaining number / total number = 100 / 100 with no chipped edges B (Acceptable): Remaining number / total number = 100 / 100 with chipped edges C (Not acceptable): Remaining number / Total number = 99~90 / 100 D (Not acceptable): Remaining units / Total units = 89 or less / 100 units (Note 3) Water resistance: Each test coated (ABS) plate was immersed in warm water at 40° C. for 240 hours, and then rinsed with water. The appearance of the test plate was evaluated according to the following criteria. A (Good): No change in appearance at all compared to the coating before the test B (Acceptable): Slight loss of gloss, swelling or discoloration is observed compared to the coating before the test, but this is at a level that will not cause any problems when used as a product. C (Fail): Slight loss of gloss, swelling or discoloration is observed compared to the coating before the test. D (Fail): Significant loss of gloss, swelling or discoloration is observed compared to the coating before the test.

[0074] Although the present invention has been described in detail and with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2019-048301) filed on March 15, 2019, the contents of which are incorporated herein by reference. [Industrial Applicability]

[0075] The coating composition of the present invention can be applied to various industrial products, particularly plastic molded products.

Claims

1. A polyester resin (A) having a glass transition temperature of −70 to 0° C., a weight average molecular weight of 2,000 to 20,000, and a hydroxyl value of 30 to 150 mgKOH / g; An acrylic resin (B1) having a glass transition temperature of 50 to 90° C., a weight average molecular weight of 5,000 to 10,000, and a hydroxyl value of 20 to 150 mgKOH / g, the acrylic resin comprising 65 to 80 mass % of methyl methacrylate (a), 5 to 35 mass % of a hydroxyl group-containing polymerizable unsaturated monomer (b), and 0 to 30 mass % of other polymerizable unsaturated monomers (c) as copolymerization components; an acrylic resin (B2) containing 20 to 45% by mass of styrene (d), 10 to 35% by mass of a hydroxyl group-containing polymerizable unsaturated monomer (e) and 20 to 70% by mass of other polymerizable unsaturated monomers (f) as copolymerization components, the resin having a glass transition temperature of 10 to 50° C., a weight average molecular weight of 10,000 to 30,000 and a hydroxyl value of 80 to 150 mgKOH / g; A blocked polyisocyanate compound (C), and At least one pigment (D) selected from the group consisting of color pigments and luster pigments. Including, A coating composition, in which the content of the acrylic resin (B1) is 15 to 40 mass%, and the content of the acrylic resin (B2) is 40 to 60 mass%, based on the total resin solid content of the polyester resin (A), the acrylic resin (B1), the acrylic resin (B2), and the blocked polyisocyanate compound (C).

2. The coating composition according to claim 1, wherein the content of the polyester resin (A) is within a range of 5 to 50 mass% based on the total resin solid content of the polyester resin (A), the acrylic resin (B1), the acrylic resin (B2), and the blocked polyisocyanate compound (C).

3. 3. The coating composition according to claim 1, further comprising at least one resin component (E) selected from the group consisting of non-aqueous dispersion resins and resin particles.

4. The coating composition according to claim 1 or 2, further comprising a polyisocyanate compound (F).

5. 3. The coating composition according to claim 1, wherein the acrylic resin (B1) has a weight average molecular weight of 5,000 to 9,000.

6. 3. The coating composition according to claim 1, wherein the acrylic resin (B2) has a glass transition temperature of 10 to 40° C., a weight average molecular weight of 10,000 to 25,000, and a hydroxyl value of 90 to 150 mg KOH / g.

7. A method for forming a coating film, which comprises coating a plastic molded article with the coating composition according to any one of claims 1 to 6.

8. The method for forming a coating film according to claim 7, further comprising coating a two-liquid type urethane clear coating on the coating film obtained by coating the coating composition according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Method for coating plastic molding

    JP2002119911A

  • Coating method

    JP2004154625A

  • Jet black multilayer coating film and method of forming the same

    JP2013193225A

  • Coating film formation method

    JP2015066543A